Ilmu fiqh - INDONESIA._DEPARTEMEN_AGAMA (Proyek Pembinaan Prasarana dan Sarana Perguruan Tinggi Agama,Dirjen Binbaga Islam Depag, 1984)
Oen, Jil.2=c.1-6; Jil.3=c.1 /tr, jil.2=c.7/tr, jil.1=c.1-2/oen, jil.3=c.2-4/why, jld 1=c3/isr, jil.1=c.4/jil.1 =c.5,jil2 =c.8/ir,jil.3,c.5-6/tr, jil.3=c.7-8/en, jil.1=c.6/en, jil.2=c.9/en, jil.3=c.9